Penambahan Probiotik dalam Pakan Terhadap Pertumbuhan Benih Ikan Lele Sangkuriang (Clarias gariepinus) pada Sistem Karamba Jaring Tancap - Safratilofa, Safratilofa; Rahmatullah, Miftahul; Harianto, Eko; Rolin, Febrina; Pangentasari, Dwinda; Maryani, Maryani; Munaeni, Waode (Universitas Batangahari Jambi, 2025)
This research aims to determine the effectiveness of adding probiotics at different doses in the rearing of Sangkuriang catfish (C. gariepinus) fry in a floating net system (KJT). The study was conducted for 40 days, from December 2024 to January 2025, at Pondok Pesantren Darul Ihsan Islamic Center, Muaro Jambi. A completely randomized design was used, consisting of four treatments with three replications: prpbiotics dose A (without probiotics), prpbiotics dose B (4 ml/kg), prpbiotics dose C (6 ml/kg), and prpbiotics dose D (8 ml/kg) of Raja Lele probiotic. The test fish used were Sangkuriang catfish fry with an initial weight of 5.46g–5.82g and a length of 8.38cm–8.63cm. The main test material was a liquid probiotic (Raja Lele). The rearing containers used were floating net cages measuring 1×1.5×1 meters. The observed parameters included growth, feed conversion ratio (FCR), survival rate (SR), and water quality. The results showed a significant increase in fish weight and length. The initial weight of 3.00g increased to 42.34g–45.91g, while the initial length of 6cm–8cm increased to 18.00cm–18.34cm. PBM ranged from 36.52g to 40.45g, PPM ranged from 9.37cm to 9.95cm, LPSB ranged from 6.84%/day to 7.36%/day, FCR ranged from 0.98 to 1.13, and SR ranged from 81.39% to 88.89%. Water quality remained within a suitable range for catfish cultivation. These results indicate that probiotics in feed have a positive effect on the growth and survival of Sangkuriang catfish